Modeling the cyclic relaxation behavior of the artificial discontinuity. Issue 2 (17th January 2021) - Zhang, Qingzhao; Luo, Zejun; Zhao, Cheng; Jang, Bo-An; Zhang, Rui
Abstract: The stress relaxation behaviors of discontinuities under cyclic loading have been rarely investigated. In this study, cyclic loading is applied to discontinuities for shear relaxation tests, in which the initial stresses are equal in each cycle. Stress relaxation patterns manifested in curves are divided into viscoelastic and viscoplastic relaxation, whose mechanisms are attributed to viscous deformation and crack activities of the stressed discontinuities. Then, relaxation behaviors under cyclic loading, associated with the modulus of cumulative deformation ( Em ) and the anti-relaxation Capacity (ARC), γ, are analyzed, it results that with the increase of cyclic times, the stress relaxed by crack activities is gradually decreasing. Accordingly, a mechanism-based relaxation model, termed as H-K//M model, is developed, which can reflect both viscoelastic and viscoplastic relaxation properties. The comparison between the fitting results and experimental data, as well as the similar variation of viscoelastic modulus, E1 and Em, viscoplastic coefficient, η and γ, show the reliability of the proposed model, which is potentially practicable for describing stress relaxation behaviors and numerical simulation of rock mass at various stress conditions.